2021
DOI: 10.3389/fpsyg.2021.647830
|View full text |Cite
|
Sign up to set email alerts
|

Obligation or Desire: Variation in Motivation for Compliance With COVID-19 Public Health Guidance

Abstract: Why do people comply with coronavirus disease 2019 (COVID-19) public health guidance? This study considers cultural-psychological foundations of variation in beliefs about motivations for such compliance. Specifically, we focused on beliefs about two sources of prosocial motivation: desire to protect others and obligation to society. Across two studies, we observed that the relative emphasis on the desire to protect others (vs. the obligation to the community) as an explanation for compliance was greater in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Even today with the widespread availability of vaccines, the most effective interventions are behavior-based interventions and they remain important with the emergence of new variants ( Bish and Michie, 2010 ; Park et al, 2010 ; Agüero et al, 2011 ; Fischhoff et al, 2018 ). However, these preventive behaviors recommended by local and national governments depend on the cooperation of the population which can substantially vary across cultural contexts ( Ai et al, 2021 ). Even with the availability of vaccines, governments depend on their citizens to cooperate in vaccine uptake and to follow continuing health guidelines till the pandemic is under control.…”
Section: Introductionmentioning
confidence: 99%
“…Even today with the widespread availability of vaccines, the most effective interventions are behavior-based interventions and they remain important with the emergence of new variants ( Bish and Michie, 2010 ; Park et al, 2010 ; Agüero et al, 2011 ; Fischhoff et al, 2018 ). However, these preventive behaviors recommended by local and national governments depend on the cooperation of the population which can substantially vary across cultural contexts ( Ai et al, 2021 ). Even with the availability of vaccines, governments depend on their citizens to cooperate in vaccine uptake and to follow continuing health guidelines till the pandemic is under control.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that adoption of COVID-19related sanitary behaviors were related to prosocial motivation (Ai et al, 2021;Jordan et al, 2021). However, these sanitary behaviors were also related to individuals' autonomous motivation (Morbée et al, 2021;Motivation barometer, 2021aMotivation barometer, , 2021bMotivation barometer, , 2021cMotivation barometer, , 2021dSchmitz et al, 2021).…”
Section: Academic Motivationmentioning
confidence: 94%
“…We address this gap by examining, in the context of the COVID‐19 pandemic, whether factors such as an individual's approval of a policy entrepreneur influences their perceived risk of contracting the virus or their adoption of recommended COVID‐19 risk mitigation behaviors. The COVID‐19 case provides a fruitful empirical context for assessing the link between entrepreneurship and individual behavior because effective infectious disease management hinges on private citizens' choices to voluntarily comply with recommended public health practices as “solutions” to the COVID‐19 problem, even if they are not formally enshrined in policy (Ai, Adams, & Zhao, 2021; Lennon et al, 2020). Thus, we use the term solution to describe an individual behavior designed to address the COVID‐19 policy problem by reducing community transmission of the virus, whether or not it was formally mandated or recommended through a policy, such as an indoor mask mandate.…”
Section: Introductionmentioning
confidence: 99%